RISET AKUNTANSI KRITIS: PENDEKATAN (NON) FEMINISME TJOET NJAK DHIEN - Ari Kamayanti (Jurnal Akuntansi Multiparadigma, 2013)
Abstract. Critical Accounting Research: Tjoet Njak Dhien (Non) Feminism Approach. This article examines the growth of feminism as a reaction to the domination of men to women. By comparing ‘men’s’ critical theories and feminism, it is found that they both still possess masculine traits. Western Feminism characters in its variety (Liberal, Radical, Marxist/Socialist, and Postmodern) are filled with the goal to overthrow oppression of men to women without regard to religiosity. This article describes the superiority of Indonesian ‘Non-Feminist’ from Aceh, Tjoet Njak Dhien, who was able to offer liberation and change by embedding the nature of Islamic women. Her lifestyle and struggle become the essence of Tjoet Njak Dhien’s Critical Theory, which is then defined into methodology for critical accounting research.Abstrak. Riset Akuntansi Kritis: Pendekatan (Non) Feminisme Tjoet Njak Dhien. Artikel ini menelaah tumbuhnya Feminisme sebagai reaksi atas dominasi laki-laki atas perempuan. Dengan membandingkan teori kritis ‘laki-laki’ dengan feminisme ditemukan kesamaan karakter maskulinitas. Karakter Feminisme Barat dalam keragamannya (Liberal, Radikal, Marxis/Sosialis, dan Posmoderen) sarat dengan tujuan penggulingan opresi laki-laki terhadap perempuan tanpa mengindahkan religiusitas. Artikel ini menjelaskan keunggulan ‘Non-Feminis’ Indonesia dari Aceh, Tjoet Njak Dhien, yang mampu menawarkan pembebasan dan perubahan dengan fitrah perempuan Islam. Gaya hidup serta perjuangannya menjadi intisari Teori Kritis Tjoet Njak Dhien yang diturunkan ke dalam metodologi untuk riset akuntansi kritis.